Inovasi Pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) untuk Menghadapi Tantangan Era Digital - Lazuardy, Dimas; Sukmana, Annisa; Japar, Muhammad (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2025)
This article analyzes the conditions and challenges of learning Pancasila and Citizenship Education (PPKn) in the digital era and identifies the benefits of innovation in overcoming these challenges. Digital technology has changed the way teaching is done, but challenges such as low digital literacy, limited infrastructure, and resistance to new methods still exist. Innovations such as e-learning, digital project-based learning, and interactive applications increase student engagement and access to learning resources. The literature review method shows that this innovation is effective in overcoming challenges, improving the quality and effectiveness of citizenship education and Pancasila values, responding to educational needs in the digital era. The purpose of this study is to improve students' understanding of Pancasila values and the importance of citizenship in a digital context, develop their digital skills, encourage creativity and innovation in learning, and facilitate collaborative learning, so that students can apply these principles actively and positively in facing the challenges of the digital era. Furthermore, the urgency of innovation in Civic and Pancasila Education (PPKn) in the digital era lies not only in the technical aspect of utilizing technology but also in shaping students’ character in accordance with Pancasila values. The integration of digital technology into learning enables the creation of collaborative, participatory, and contextual learning models connected to students’ real-life experiences. Through this study, it can be concluded that the success of PPKn education in the digital era largely depends on teachers’ ability to integrate technology with appropriate pedagogical approaches, while simultaneously equipping students with 21st-century skills rooted in Pancasila values.